Tantangan dan Upaya Penghargaan terhadap Perbedaan melalui Kegiatan Lintas Agama : Studi Kasus di SDN Barambai Kolam Kanan 1 - Irsalina, Dina; Suriansyah, Ahmad; Harsono, Arta Mulya Budi; Iskandar, Bagus Aulia; Mubarok, Mubarok (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
Diversity is one of the main characteristics of Indonesian society, encompassing differences in ethnicity, religion, culture, and socio-economic backgrounds. Indonesia, as a nation rich in cultural and religious diversity, faces challenges in fostering tolerance and unity, particularly in the school environment. SDN Barambai Kolam Kanan 1 is an elementary school striving to break the stigma that students from different religious backgrounds are difficult to unite. This article aims to identify challenges and evaluate efforts to appreciate differences through interfaith routine activities. Using a qualitative approach, this study involves in-depth interviews, direct observations, and supporting documentation. The results show that interfaith activities, such as joint celebrations of religious holidays, significantly contribute to enhancing tolerance among students. However, obstacles such as resistance from certain groups and entrenched stereotypes still require strategic solutions.